(untitled) (International Journal of Occupational Safety and Health, 2018)
Background: Cognitive ergonomics relates with studies related to knowledge, knowledge acquisition skills and other factors. In the modern days, the workers are exposed to a work, which demands cognitive skill along with physical ability. Objectives: Aim of the present study is to evaluate the effect of physical exertion along with thermal stress on the cognitive performance among the adolescent farmers through. In the present study, cognitive performance was evaluated through physical exertion along with thermal stress among the adolescent farmers. This cross-sectional study was performed during 2017 -18 among the randomly selected 50 male and 50 female adolescent farmers from the various village of Hooghly District at West Bengal, India. Before conducting the study, legal guardian consent was taken. Prior permission and ethical approval was also obtained from local community leaders as well as relevant authorities before commencement of the study. The memory test or cognitive ability test was done by the Immediate Recovery Test. In cognitive ability test, three pictorial cards were prepared having same length; each of the cards had 15 pictorials. Different pictures card was shown to all the subjects for 15 minutes in resting condition. Immediately after 15 minutes all the subjects were asked to recall the pictures within the 3 minutes. Then, evaluation was undertaken in presence of the subjects. Results: The result of the study shows that the farmers performed strenuous activity by which they do the more error in cognitive function test than control subjects. This may be due to increase in strenuous activity in agricultural sector by increasing the heart rate (physiological stress) which may decrease the cognitive function among the farmers in compare to control subjects. Conclusion: The study concludes that intense fatigue producing or highly strenuous agricultural activity lead to an increase in the number as well as in the percentage of wrong answers in the cognitive test. On the other hand, moderate type of agricultural results in a decrease in the number as well as in the percentage of wrong answers and there is an improvement in the cognitive performance.